2020
DOI: 10.3390/antiox10010042
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities of Light-Emitting Diode (LED) as Key to Modulate Antioxidant Compounds in Plants. A Review

Abstract: Plant antioxidants are important compounds involved in plant defense, signaling, growth, and development. The quantity and quality of such compounds is genetically driven; nonetheless, light is one of the factors that strongly influence their synthesis and accumulation in plant tissues. Indeed, light quality affects the fitness of the plant, modulating its antioxidative profile, a key element to counteract the biotic and abiotic stresses. With this regard, light-emitting diodes (LEDs) are emerging as a powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 239 publications
(204 reference statements)
3
55
1
Order By: Relevance
“…In fact, in a review concerning LED lighting as a key to modulate antioxidant compounds in plants, Loi et al [59] stated that B, R and FR lights had shown to be able to increase the TPC and TFC in different plant commodities, and that the regulation of TPC and TFC by LEDs can be performed directly by inducing the expression of the key enzyme and indirectly by increasing the shikimic acid as precursor molecule [60]. Nevertheless, besides light intensity, their contents also depend upon plant species, cultivars and timing of LED exposure [59]. It is well established that salinity can enhance the synthesis of secondary metabolites in plants [61], producing reactive oxygen species, which are harmful to plant cells.…”
Section: Total Phenol Content Total Flavonoids Content and Total Antioxidant Capacitymentioning
confidence: 99%
“…In fact, in a review concerning LED lighting as a key to modulate antioxidant compounds in plants, Loi et al [59] stated that B, R and FR lights had shown to be able to increase the TPC and TFC in different plant commodities, and that the regulation of TPC and TFC by LEDs can be performed directly by inducing the expression of the key enzyme and indirectly by increasing the shikimic acid as precursor molecule [60]. Nevertheless, besides light intensity, their contents also depend upon plant species, cultivars and timing of LED exposure [59]. It is well established that salinity can enhance the synthesis of secondary metabolites in plants [61], producing reactive oxygen species, which are harmful to plant cells.…”
Section: Total Phenol Content Total Flavonoids Content and Total Antioxidant Capacitymentioning
confidence: 99%
“…YP showed the lowest vitamin C content, while RP and RC showed similar values ( Table 3 ). Moreover, Loi et al [ 39 ] reported that vitamin C synthesis is light dependent and its synthesis depends on light intensity, quality, and penetration into the canopy. During this study, the vitamin C content was influenced by the interaction of SL treatment with genotypes ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The spectral output of the source should, therefore, match the plant's photosynthesis and photomorphogenesis requirement [10]. Fluorescent, metal-halide, high-pressure sodium, and incandescent lamps were developed for human lighting requirements and are, therefore, not ideal light sources for plants, whereas LEDs emit specific wavelengths and can be matched to plant needs [11]. The first LEDs used in plant research were based on a gallium-aluminium-arsenide substrate (GaAIAs) with an emission peak range from 630 to 680 nm (Table 3) [10].…”
Section: Led and Light Spectramentioning
confidence: 99%
“…Summary of photoreceptors involved in physiological responses of plants to different light spectra. Semiconductors in LEDs and their emission spectra[11].…”
mentioning
confidence: 99%